2004
DOI: 10.1007/s00253-003-1471-8
|View full text |Cite
|
Sign up to set email alerts
|

Diglucosyl-glycerolipids from the marine sponge-associated Bacillus pumilus strain AAS3: their production, enzymatic modification and properties

Abstract: The marine strain Bacillus pumilus strain AAS3, isolated from the Mediterranean sponge Acanthella acuta, produced a diglucosyl-glycerolipid, 1,2-O-diacyl-3-[beta-glucopyranosyl-(1-6)-beta-glucopyranosyl)]glycerol, with 14-methylhexadecanoic acid and 12-methyltetradecanoic acid as the main fatty acid moieties (GGL11). On a 30 l scale, using artificial seawater supplemented with glucose (20 g/l), yeast extract (10 g/l), and suitable nitrogen/phosphate sources, growth-associated glycoglycerolipid production reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Antitumor promoting studies showed that the diglucosyl-glycerol GG11 strongly inhibited the growth of the tumor cell lines HM02 and Hep G2. Thus, it indicates the potential inhibitory activity of the compound with carbohydrate/glycerol backbone [116]. Twenty nine marine bacterial strains were isolated from the sponge Hymeniacidon perlevis at Nanji Island (China Sea), and the antimicrobial screening showed that eight strains inhibited the growth of terrestrial microorganisms.…”
Section: Sponges and Associated Microbes Involved In Drug Productionmentioning
confidence: 99%
“…Antitumor promoting studies showed that the diglucosyl-glycerol GG11 strongly inhibited the growth of the tumor cell lines HM02 and Hep G2. Thus, it indicates the potential inhibitory activity of the compound with carbohydrate/glycerol backbone [116]. Twenty nine marine bacterial strains were isolated from the sponge Hymeniacidon perlevis at Nanji Island (China Sea), and the antimicrobial screening showed that eight strains inhibited the growth of terrestrial microorganisms.…”
Section: Sponges and Associated Microbes Involved In Drug Productionmentioning
confidence: 99%
“…Glycoglycerolipids related to testacosides have been isolated from cultures of a wide variety of bacteria obtained from different sources, such as the pathogen Rothia mucilaginosa (Pasciak et al 2004), Bacillus pumilus (Ramm et al 2004 ), Microccocus luteus (Pakkiri et al 2004 ), and the marine-derived Bacillus licheniformis 09IDYM23 (Tareq et al 2015 ). Unusual glycoglycerolipids diacylated at both 3 and 6′ positions have already been isolated from bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a pressing need to intensify the search for novel biosurfactant-producing microorganisms. They can be found in soil [42][43][44][45], oil [46][47][48][49][50][51], water [52][53][54][55], and food [56][57][58][59]. The synthesis of biosurfactants is influenced by various factors, including watersoluble/insoluble carbon sources, nitrogen sources, pH, temperature, carbon-to-nitrogen (C/N) ratio, agitation, and oxygen availability [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%